Risk and adaptation of socio-ecological systems to global change in the dry forests of Northeastern South America - Niemeyer, Julia; Resende, Fernando M.; Moura Lima, Edberto; Vale, Mariana M. (Frontiers in Ecology and Evolution, 2025)
Northeastern South America is among the continent’s most climate-vulnerable regions, marked by low socioeconomic indices and high climatic hazards, particularly droughts. We did a climate change risk assessment for the region’s most important watershed, incorporating the three components of risk — hazards, exposure, and vulnerability — a procedure rarely done. We analyzed land use and climate change hazards, human population exposure, and socio-environmental vulnerability by mapping ecosystem services and socioeconomic indices. We pinpointed 15 high-risk municipalities out of 455 in the study region, suggesting existing ecosystem-based adaptation (EbA) policies at the municipal level to reduce vulnerability, coupled with watershed-scale technological solutions. We also provide an online dashboard with an interactive map to facilitate results visualization and support the decision-making process. Our proposed approach is transferable globally, focusing on enhancing the effectiveness of EbA in responding to climate change.